2017
DOI: 10.1007/s13197-017-2831-1
|View full text |Cite
|
Sign up to set email alerts
|

Effects of dough mixing time before adding konjac glucomannan on the quality of noodles

Abstract: In this study, effects of 5% konjac glucomannan (KGM) blended with low-protein flour at different dough mixing duration on the properties of dough and noodles were investigated. To prepare the KGM noodle samples, 5% KGM was added after low-protein flour mixed with water for 0, 2 and 4 min, respectively. The three samples above were defined as T KGM, T KGM and T KGM noodle samples, respectively. The results revealed that the elastic modulus (') and viscous modulus (″) of dough both increased with extending doug… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
8
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 21 publications
(10 citation statements)
references
References 33 publications
1
8
0
Order By: Relevance
“…Konjac flour is a natural, gluten‐free mannose polysaccharide that is found in the konjac plant ( Amorphophallus konjac ). Konjac flour is the most viscous food gum in nature and can be used as a thickening agent in food preparation (Gómez et al ) or as a perfect additive to diet food (Vuksan et al ; Zhao et al ; Devaraj et al ). Konjac glucomannan is a valuable resource for the preparation of manno‐oligosaccharides (MOSs).…”
Section: Introductionmentioning
confidence: 99%
“…Konjac flour is a natural, gluten‐free mannose polysaccharide that is found in the konjac plant ( Amorphophallus konjac ). Konjac flour is the most viscous food gum in nature and can be used as a thickening agent in food preparation (Gómez et al ) or as a perfect additive to diet food (Vuksan et al ; Zhao et al ; Devaraj et al ). Konjac glucomannan is a valuable resource for the preparation of manno‐oligosaccharides (MOSs).…”
Section: Introductionmentioning
confidence: 99%
“…[ 29 ] After the start of pasting, due to the increase in the temperature, the hydrogen bonds between starch molecules were broken. [ 22 ] This led to KGM's interactions with leached amylose and low molecular weight amylopectin in starch granules. This resulted in an increase in the viscosity of the system.…”
Section: Resultsmentioning
confidence: 99%
“…[ 20 ] reported that KGM effectively protected the quality of rice starch gel in the freeze‐thaw cycles by postponing retrogradation. Incorporation of KGM positively influenced the rheological properties of wheat dough, [ 21 ] the texture of wheat noodles, [ 22 ] and the physicochemical properties and texture of low‐fat and skimmed yogurt. [ 23 ] However, the effect of KGM on starches at the molecular level, and its effect on the structure and functional characteristics of frozen dough are rarely investigated.…”
Section: Introductionmentioning
confidence: 99%
“…Cooking losses value in optimum restructured rice was higher because optimum restructured rice is partially gelatinized, because some polysaccharide losses when it is cooked and it is also the effect of adding glucomannan which is certainly water-soluble, so that some glucomannan which is not bound well with starch will be losses when it is cooked. L. Wang et al (2016) stated that during extrusion process, the temperature and the screw speed affects the quality and texture of brown rice pasta and also (Zhao et al, 2017) reported that when greater konjac glucomannan (KGM) was substituted with wheat flour, dough mixing increased the cooking loss of noodle samples, suggesting that a greater amount of exudates escaped from the dough system during starch granule gelatinization.…”
Section: Cooking Characteristicsmentioning
confidence: 99%